Anthropology, by comparison - Gingrich, André; Fox, Richard G. (Richard Gabriel), 1939- (Routledge, 2002)
An international group of anthropologists take a fresh look at various neglected approaches to comparison and present new approaches that are relevant to the globalized world of the twenty first century.